Depth‐dependent atomic valence determination by synchrotron techniques. (20th September 2018) - Trappen, Robbyn; Zhou, Jinling; Tra, Vu Thanh; Huang, Chih-Yeh; Dong, Shuai; Chu, Ying-Hao; Holcomb, Mikel B.
Abstract : A combination of bulk‐ and surface‐sensitive X‐ray‐absorption techniques are used in conjunction with model Hamiltonian calculations in order to experimentally determine the depth‐dependent valence in La0.7 Sr0.3 MnO3 (LSMO) thin film. Abstract : The properties of many materials can be strongly affected by the atomic valence of the contained individual elements, which may vary at surfaces and other interfaces. These variations can have a critical impact on material performance in applications. A non‐destructive method for the determination of layer‐by‐layer atomic valence as a function of material thickness is presented for La0.7 Sr0.3 MnO3 (LSMO) thin films. The method utilizes a combination of bulk‐ and surface‐sensitive X‐ray absorption spectroscopy (XAS) detection modes; here, the modes are fluorescence yield and surface‐sensitive total electron yield. The weighted‐average Mn atomic valence as measured from the two modes are simultaneously fitted using a model for the layer‐by‐layer variation of valence based on theoretical model Hamiltonian calculations. Using this model, the Mn valence profile in LSMO thin film is extracted and the valence within each layer is determined to within an uncertainty of a few percent. The approach presented here could be used to study the layer‐dependent valence in other systems or extended to different properties of materials such as magnetism.